Pengaruh Penyimpanan Terhadap Kadar Sediaan Injeksi Mecobalamin Dengan Metode Spektrofotometri UV-VIS - fathul hidayatul; Deny Budi L; Erna Fitriany (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
This scientific paper examines how mecobalamin injection preparations will be affected by the length of storage and can lead to a decrease in drug quality to drug damage. The material used for this research is mecobalamin pro-analysis from PT. Kalbe, chocolate ampoule injection mecobalamin, and aquadest. This research is an experimental study, which aims to determine the effect of storage time on the physical quality of mecobalamin injection preparations in brown ampoules using UV-Vis spectrophotometry method. The purpose of this study was to determine the levels of mecobalamin injection preparations that were affected by light for 24 hours with storage durations of 5 days, 10 days, 15 days, and 0 days as a control for comparison. A series of tests from this study concluded that temperature, humidity, light, the effect of storage time, and sample preparation affected the levels of mecobalamin injection preparations. Based on the determination of the concentration of mecobalamin injection in the test solution with different storage times, the results were not constant due to a decrease in levels, when compared to the control.